2015
DOI: 10.1136/annrheumdis-2015-eular.1597
|View full text |Cite
|
Sign up to set email alerts
|

SAT0377 Interferon Gamma-Inducible Protein 16 (IFI16) in Primary SjÖgren's Syndrome: A Novel Player in Disease Pathogenesis?

Abstract: BackgroundAlthough the pathogenesis of primary Sjögren's syndrome (pSS) is not fully elucidated, several studies suggest that the interferon (IFN) signature is involved in both induction and perpetuation of the disease (1). The interferon gamma-inducible protein 16 (IFI16), normally expressed in cell nuclei, may be overexpressed, mislocalized in the cytoplasm and secreted in the extracellular milieu in several autoimmune disorders, including systemic lupus erythematosus and systemic sclerosis. This leads to to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…[30][31][32]34 In some of these previous studies, increased aberrant IFI16 expression has been demonstrated in target tissues, including the skin in SLE and the salivary glands in SjS. 33,35 Consistent with these findings and a previous report by Vanhove et al, we were able to demonstrate aberrant epithelial IFI16 expression in inflamed colon mucosa from both CD and UC patients by immunohistochemistry. 12 Considering that: i) gut epithelial cells do not express IFI16 in the normal setting; ii) IFI16 is a nuclear DNA sensor for pathogen exogenous DNA; and iii) IBD likely results from an aberrant immune response against micro-organisms, bacteria or viruses that are able to invade cells of the gut mucosa and release or produce exogenous dsDNA, it is not surprising that pattern recognition receptors, such as IFI16, are aberrantly upregulated in these patients and may trigger the production of specific autoantibodies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…[30][31][32]34 In some of these previous studies, increased aberrant IFI16 expression has been demonstrated in target tissues, including the skin in SLE and the salivary glands in SjS. 33,35 Consistent with these findings and a previous report by Vanhove et al, we were able to demonstrate aberrant epithelial IFI16 expression in inflamed colon mucosa from both CD and UC patients by immunohistochemistry. 12 Considering that: i) gut epithelial cells do not express IFI16 in the normal setting; ii) IFI16 is a nuclear DNA sensor for pathogen exogenous DNA; and iii) IBD likely results from an aberrant immune response against micro-organisms, bacteria or viruses that are able to invade cells of the gut mucosa and release or produce exogenous dsDNA, it is not surprising that pattern recognition receptors, such as IFI16, are aberrantly upregulated in these patients and may trigger the production of specific autoantibodies.…”
Section: Discussionsupporting
confidence: 90%
“…In the same cohort, we also evaluated anti-GP2 antibody levels and confirmed the findings previously reported. [35][36][37][38][39][40][41] Anti-GP2 IgG subtype titres were significantly increased in CD as was the IgA subtype although to a lesser extent compared with UC and HC, with a statistically significant correlation between IgG and IgA subtype expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations